Operationalizing evolutionary transitions in individuality. Issue 1920 (12th February 2020) - Carmel, Yohay; Shavit, Ayelet
Abstract : Evolutionary transitions in individuality (hereafter, ETIs), such as the transition to multi-cellularity and the transition to social colonies, have been at the centre of evolutionary research, but only few attempts were made to systematically operationalize this concept. Here, we devise a set of four indicators intended to assess the change in complexity during ETIs: system size, inseparability, reproductive specialization and non-reproductive specialization. We then conduct a quantitative comparison across multiple taxa and ETIs. Our analysis reveals that inseparability has a crucial role in the process; it seems irreversible and may mark the point where a group of individuals becomes a new individual at a higher hierarchical level. Interestingly, we find that disparate groups demonstrate a similar pattern of progression along ETIs.